Financial Literacy, Lifestyle, Dan Financial Technology Terhadap Financial Behavior Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Slamet Riyadi Surakarta - Ita Mariatun Nisa’; Rina Susanti (Teewan Journal Solutions, 2026)
This study was designed to empirically test the significance of the influence of financial literacy (X₁), lifestyle (X₂), and financial technology (X₃) on the financial behaviour (Y) of students at the Faculty of Economics and Business, Slamet Riyadi University, Surakarta. The methodology used was a quantitative survey of 100 respondents selected using quota sampling techniques. The data were analysed using multiple linear regression. The results of the study concluded as follows: (1) Financial literacy and lifestyle partially have a significant effect on financial behaviour. (2) Financial technology does not have a significant effect on financial behaviour. (3) Simultaneously, the F test (p=0.000) shows that the three independent variables have a significant effect on the dependent variable, indicating the validity of the model. (4) The coefficient of determination (Adjusted R2) is 0.231, which means that the simultaneous contribution of the three independent variables to the dependent variable is 23.1%, while the remaining 76.9% is influenced by other variables not examined.